2011
DOI: 10.1007/s10741-011-9231-9
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory parameters of cardiac and kidney dysfunction in cardio-renal syndromes

Abstract: "Cardio-Renal Syndromes" (CRS) are disorders of the heart and kidneys in which acute or chronic dysfunction in one organ may induce acute or chronic dysfunction of the other. The pathophysiology of CRS is complex, and there is accumulating evidence that various novel biomarkers are useful for diagnosis, prognostication, and risk stratification in patients with heart failure and chronic kidney disease (CRS). When both the heart failure (HF) and CKD occur together, it is important to have biomarkers that are abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 55 publications
0
24
1
1
Order By: Relevance
“…Furthermore, we tried to elucidate gains in information by the new markers and interferences of the diagnostic performance by leukocyturia or hematuria. Studies in children and adults have shown that uNGAL is rapidly and massively expressed in well-defined cases of AKI [8,9]. Besides predicting AKI, NGAL may be involved in the pathophysiological process of chronic renal diseases, such as polycystic kidney disease and glomerulonephritis as well as several types of renal tumors [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we tried to elucidate gains in information by the new markers and interferences of the diagnostic performance by leukocyturia or hematuria. Studies in children and adults have shown that uNGAL is rapidly and massively expressed in well-defined cases of AKI [8,9]. Besides predicting AKI, NGAL may be involved in the pathophysiological process of chronic renal diseases, such as polycystic kidney disease and glomerulonephritis as well as several types of renal tumors [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Urinary NGAL (uNGAL) likely plays a critical role in host defense by chelating iron-siderophore complexes and is rapidly and massively expressed in AKI as shown by numerous studies [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, GFR is prone to several biases linked to the formula used for its calculation (age, body weight and patient setting). The recognition of biomarkers for the early diagnosis of kidney injury is now becoming a research priority [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in most of these studies, there has been minimal to no adjustment for potential confounders, such as CKD. It is relevant therefore, that in AHF, discharge plasma NGAL level was a stronger predictor of 30-day outcome than BNP, the guideline-supported standard for risk prediction (42), even after adjustment for renal function. If reproduced in other studies, one could speculate that a high NGAL at the time of discharge for AHF might, at a minimum, be a signal for early follow-up.…”
Section: Discussionmentioning
confidence: 99%